Synthesis and preliminary characterization of octakis (chloropropyldimethylsiloxy) octasilsesquioxane - Carmo, Devaney Ribeiro Do [UNESP]; Dias Filho, Newton Luiz [UNESP]; Stradiotto, Nelson Ramos [UNESP] (ABM, ABC, ABPol, 2004)
Octakis (hydridodimethylsiloxy) octasilsesquioxane was hydrosilated with allyl chloride using Spiers catalyst (H2PtCl6). This reaction was monitored using FT-IR spectroscopy. The synthesized product was characterized by 13C, 29Si NMR (MAS), SEM, FT-IR, Thermogravimetric techniques. The three propyl groups alpha, beta, gamma, (to the terminal silicon atom), associated of an allyl chloride, were clearly seen in the 13C NMR (alpha-CH2 at 31.8; beta-CH2 at 37.7; gamma-CH2 at 50.1 ppm). In addition, the 29Si NMR spectrum of the final product, exhibits three Q signals for Q type silicon attributed to Q² (-90.1) Q³ (-100.2) and Q4 (-111.3ppm). The presence of allyl chloride substitutes in octameric cube confers a relative porosity and thermal stability to the material.
Keywords: Octakis (chloropropyldimethylsiloxy) octasilsesquioxane; spherosiloxane